Improvement of Agricultural Technologies Agriculture and Increasing Volume of Pastures in the Conditions of Lack of Water - Niyetbay Baynazarovich, Reimov; Zhaksybay, Kalimbetov; Omirbay, Reimov; Venus, Utepbergenova; Feruza, Reimova (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, the Republic of Karakalpakstan often has low water levels. According to the forecasts of international experts, this phenomenon may happen again in the future, and the level of water supply can still be reduced by 10-15%. Therefore, it will be advisable to draw up plans for the distribution of crops in accordance with the forecast of the expected degree of water availability.